Isolasi dan Identifikasi Molekuler Candida albicans dari Sekret Keputihan Menggunakan Metode PCR - Anggun Sophia; Suraini Suraini; Vetra Susanto; Niken Niken (Stikes Syedza Saintika Padang, 2025)
Candida albicans is one of the major pathogenic fungi responsible for pathological vaginal discharge in women. This study aimed to isolate and identify C. albicans from vaginal discharge samples using conventional methods and molecular confirmation based on Polymerase Chain Reaction (PCR). A total of five vaginal discharge samples were collected and cultured on selective media. The isolation results showed that four samples (SC2–SC5) exhibited colony characteristics consistent with C. albicans, while one sample (SC1) demonstrated morphological features suggestive of the genus Aspergillus. Conventional identification through macroscopic and microscopic examination, as well as the germ tube test, confirmed that the four isolates were strong candidates for C. albicans. Molecular identification using specific primers targeting the Internal Transcribed Spacer (ITS) region indicated that only one isolate produced a distinct DNA band at approximately ±600 bp, which corresponds to the specific ITS fragment size for C. albicans. The SC3 isolate was confirmed as C. albicans based on molecular analysis. These findings highlight the importance of PCR-based confirmation to improve the accuracy of fungal identification, particularly in cases of pathological vaginal discharge.